Gambaran Fungsi Kognitif pada Pasien Epilepsi di Poliklinik Saraf RSUP Prof. Dr. R.D. Kandou Manado - Sigar, Raymond J.; Kembuan, Mieke A.H.; Mahama, Corry N. (Universitas Sam Ratulangi, 2017)
Abstract: Epilepsy is one of most common neurological disorders that causes cognitive decline. This stuayd was aimed to ascertain the overview of cognitive function in epilepsy patients at the Neurology Clinic of Prof Dr. R. D. Kandou Hospital Manado. This was a prospective descriptive study with a cross-sectional design. Data were obtained through anamnesis and direct test to 35 epileptic patients by using questionnaire, MMSE, and Ina-MoCA instruments in the Neurology Clinic of Prof. Dr. R. D. Kandou Hospital Manado from October to November 2017. The results MMSE showed 77.10% of patients had normal cognitive function. Meanwhile, the Ina-MoCa resulted in 89% of respondents suffering from cognitive decline. Conclusion: There were impaired cognitive functions ranging from mild to severe in epileptic patients that could affect their quality of life and functional status.Keywords: epilepsy, cognitive functionÂ Abstrak: Epilepsi adalah salah satu gangguan neurologik yang terbanyak yang menyebabkan gangguan fungsi kognitif. Penelitian ini bertujuan untuk mengetahui gambaran fungsi kognitif pada pasien epilepsi di Poliklinik Saraf RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ialah deskriptif prospektif dengan desain potong-lintang. Pengumpulan data diperoleh melalui wawancara dan pengujian langsung terhadap pasien epilepsy yang berjumlah 35 orang. Penelitian ini menggunakan kuesioner, serta instrumen MMSE dan Ina-MoCA dilakukan di Poliklinik Saraf RSUP Prof Dr. R. D. Kandou Manado sejak bulan Oktober s/d November 2017. Hasil pemeriksaan dengan MMSE menunjukkan 77,10% dari pasien dengan fungsi kognitif normal sedangkan pemeriksaan dengan Ina-MoCA menunjukkan 89% dari pasien mengalami gangguan fungsi kognitif. Simpulan: Terdapat gangguan fungsi kognitif ringan-berat pada pasien epilepsi yang dapat memengaruhi kualitas hidup dan status fungsional.Kata kunci: epilepsi, fungsi kogntif